2020
DOI: 10.1016/j.childyouth.2020.105429
|View full text |Cite
|
Sign up to set email alerts
|

Service needs of young people affected by adverse childhood experiences (ACEs): A systematic review of UK qualitative evidence

Abstract: Highlights Emotional support through supportive relationships with adults is valued highly. How services are delivered is just as important as what is delivered. Flexible and dependable services give a much-needed sense of control and autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 51 publications
1
52
0
Order By: Relevance
“…An important means of ascertaining the service needs of people affected by ACEs is to ask them directly about what they need and thereby develop a more complete understanding of what might be helpful (Whitehead et al, 2019). Children's views are especially valuable as they can draw attention to needs and concerns of which adults may be unaware (Lester et al, 2020). In an extensive review of multiple qualitative research study consultations with young people across a broad range of ACEs, Lester and colleagues (2020) found that young people appreciate both emotional and practical support, together with supportive relationships with trusted adults.…”
Section: What Is the Evidence That Familial/individual Level Interven...mentioning
confidence: 99%
See 4 more Smart Citations
“…An important means of ascertaining the service needs of people affected by ACEs is to ask them directly about what they need and thereby develop a more complete understanding of what might be helpful (Whitehead et al, 2019). Children's views are especially valuable as they can draw attention to needs and concerns of which adults may be unaware (Lester et al, 2020). In an extensive review of multiple qualitative research study consultations with young people across a broad range of ACEs, Lester and colleagues (2020) found that young people appreciate both emotional and practical support, together with supportive relationships with trusted adults.…”
Section: What Is the Evidence That Familial/individual Level Interven...mentioning
confidence: 99%
“…Children's views are especially valuable as they can draw attention to needs and concerns of which adults may be unaware (Lester et al, 2020). In an extensive review of multiple qualitative research study consultations with young people across a broad range of ACEs, Lester and colleagues (2020) found that young people appreciate both emotional and practical support, together with supportive relationships with trusted adults. This finding regarding supportive relationships with trusted adults is reinforced in another systematic review by Whitehead and colleagues (2019) who reported that young people consistently see the role of trusted adults as helpful and one that leads to positive outcomes, such as attaining better educational results, developing improved confidence, and decreasing their symptoms of anxiety and depression.…”
Section: What Is the Evidence That Familial/individual Level Interven...mentioning
confidence: 99%
See 3 more Smart Citations